Fenomena Golput Pada Pilkada Pati 2011 - Dewi Masitoh; Susilo Utomo; Wiwik Widayati (Journal of Politic and Government Studies, 2013)
Abstention phenomenon that occurs in the Pati Regional Head Election 2011 was ageneral election officer who has the highest number abstentions in Central Java at the time. Thestudy was conducted to analiyze the phenomenon of non-voters who happen to Pati Election2011 by using quantitative descriptive approach or talk about the frequency. This method is asurvey study in which the authors took a simple of the population and the use of questionnairesas the main data collection tool. Descriptive research is intended to careful measurement ofcertain social phenomena. Authors develop the concept and to compile fakt, but do not dopengjian hyphotesis, the result of the survey can also be used to hold a certain predictions aboutsocial phenomena.Abstensions of voter that occurs in Pati Election can be seen from the technical aspect,political aspect, ideological aspect and oersonal identity. This research found that the technicalaspect have to be main reason why Pati’s people unwilling to give vote. The technical aspect isconstraints that make people couldn’t voting, such as have other activities at the same timeelection day so could not come the polls. On the political aspects of behavior such as non-votershave no reason to believe the party, candidate/candidates or do not believe in change for thebetter. Meanwhile, if viewed from the aspect of one’s identity may be seen by religion, level ofeducation, age, gender and others. For example, if viewed in terms of religion for non-votersbecause someone decided that the party was not selected as candidate expected/ candidate, forexample in someone who is Christian tends not vote for a party that carried Islam as PPP, PKBwhile generally on the wing nationalist candidate or political party judged less respresentatif toaccommodate their asoirations, then the non-voters will be the final option is taken.